Positive electrode material, electrochemical device, and electronic device

CN116830311BActive Publication Date: 2026-10-16NINGDE AMPEREX TECHNOLOGY LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202280010318.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-19
Publication Date
2026-10-16
Estimated Expiration
2042-04-19

AI Technical Summary

Technical Problem

在高电压、高脱锂量下,正极材料表面释氧和结构相变的问题也充分暴露出来,带来电池循环跳水以及产气等问题

Benefits of technology

[0023] This application improves the structural stability of the cathode material under high temperature and high pressure, as well as its kinetic performance under high rate charge and discharge conditions, by introducing iodine ion lattice doping into the surface layer of the cathode material and controlling the molar ratio of iodine to nickel within the range of 0.25 to 1.5. This reduces the gas generation during storage under high temperature and high pressure and the temperature rise under high rate charge and discharge conditions in the electrochemical device, thereby improving the overall performance of the electrochemical device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116830311B_ABST
    Figure CN116830311B_ABST
Patent Text Reader

Abstract

The application provides a positive electrode material, which comprises a substrate and a first region on the surface of the substrate, and the molar ratio of iodine elements and nickel elements in the first region is 0.25-1.5. The application introduces iodine ion lattice doping in the surface layer of the positive electrode material, and controls the molar ratio of iodine elements and nickel elements in the range of 0.25-1.5, so that the structural stability of the positive electrode material under high temperature and high pressure and the kinetic performance of the positive electrode material under large-rate charging and discharging conditions are effectively improved, the storage gas generation of an electrochemical device under high temperature and high pressure and the temperature rise of the electrochemical device under large-rate charging and discharging conditions are reduced, and the comprehensive performance of the electrochemical device is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of energy storage, specifically to a cathode material, an electrochemical device, and an electronic device. Background Technology

[0002] With the widespread adoption of consumer electronics such as laptops, mobile phones, tablets, power banks, and drones, the requirements for their batteries are becoming increasingly stringent. For example, batteries are not only required to be lightweight, but also to have high capacity and long lifespan. Lithium-ion batteries, with their outstanding advantages such as high energy density, good safety, no memory effect, and long lifespan, have already gained a mainstream position in the market.

[0003] In pursuit of higher energy density, lithium-ion batteries have been continuously developed towards increasing voltage and lithium removal rate. However, under high voltage and high lithium removal rates, the problems of oxygen release and structural phase transitions on the cathode material surface are fully exposed, leading to issues such as rapid battery cycle degradation and gas generation. Furthermore, the poor kinetics of ternary cathode materials limit their capacity utilization, resulting in a series of problems such as severe battery temperature rise under high-rate charge-discharge conditions. Summary of the Invention

[0004] In view of the above-mentioned problems existing in the prior art, this application provides a cathode material and an electrochemical device including the cathode material to improve the structural stability of the cathode material under high temperature and high pressure and the kinetic performance under high rate charge and discharge conditions, thereby reducing the storage gas generation of the electrochemical device under high temperature and high pressure and the temperature rise under high rate charge and discharge conditions, and improving the overall performance of the electrochemical device.

[0005] In a first aspect, this application provides a cathode material comprising a substrate and a first region located on the surface of the substrate, wherein the molar ratio of iodine to nickel in the first region is 0.25 to 1.5. Cathode ternary materials primarily generate capacity through the valence variation of nickel and cobalt. Under deep delithiation, the oxygen ion activity on the material surface is high, easily leading to side reactions with the electrolyte. On the one hand, spinel readily forms on the material surface, inhibiting lithium ion diffusion; on the other hand, surface side reactions further increase interfacial impedance and simultaneously cause gas generation on the material surface. The inventors of this application have discovered that by introducing iodine ion lattice doping into the surface layer of the cathode material and controlling the molar ratio of iodine to nickel to be 0.25 to 1.5, lithium iodate can be locally formed. Since lithium iodate possesses extremely strong oxidation resistance, as an external protective layer, it can improve the interfacial stability of the cathode material with the electrolyte under high temperature and high voltage conditions, thereby suppressing gas generation during storage in electrochemical devices under high temperature and high pressure conditions and improving the high-temperature cycling performance of electrochemical devices. At the same time, it can reduce the valence state of the surface transition metal redox couple, increase the electron jumping path, and improve the electronic conductivity, thereby improving the kinetic performance of the cathode material and thus improving the temperature rise of the electrochemical device under high-rate charge and discharge conditions.

[0006] According to some embodiments of this application, the molar ratio of iodine to nickel in the first region is 0.5 to 1.5.

[0007] According to some embodiments of this application, the first region includes a second region, and the second region includes lithium iodate.

[0008] According to some embodiments of this application, the first region further includes a third region, wherein the third region includes nickel iodide.

[0009] In some embodiments, the third region is located between the substrate and the second region. In this case, the second region, which includes lithium iodate on the outer side, has stronger oxidation resistance and can further improve the interfacial stability of the cathode material with the electrolyte under high temperature and high voltage, thereby suppressing gas generation during storage in the electrochemical device under high temperature and high pressure conditions and improving the high temperature cycling performance of the electrochemical device.

[0010] According to some embodiments of this application, the thickness of the second region is H2, wherein 10nm ≤ H2 ≤ 60nm. According to some embodiments of this application, the thickness of the third region is H3, wherein 2nm ≤ H3 ≤ 60nm. In this case, the thicknesses of the second and third regions are appropriate, which can improve the interfacial stability of the cathode material with the electrolyte under high temperature and high voltage while reducing the impact on the energy density of the electrochemical device.

[0011] According to some embodiments of this application, in the region from the surface of the positive electrode material to a depth of 2 μm from the surface of the positive electrode material, the molar ratio of iodine to nickel gradually decreases along the depth direction of the positive electrode material.

[0012] According to some embodiments of this application, the XRD pattern of the cathode material shows a characteristic peak of 2θ in the range of 25.0° to 26.0°. In this application, the characteristic peak of 2θ in the range of 25.0° to 26.0° is the diffraction peak of surface lithium iodate. At this time, the surface lithium iodate can better protect the surface of the substrate, improve the interfacial stability of the cathode material with the electrolyte under high temperature and high voltage, thereby suppressing gas generation during storage in the electrochemical device under high temperature and high pressure conditions and improving the high temperature cycling performance of the electrochemical device.

[0013] According to some embodiments of this application, in the XRD pattern of the cathode material, the peak intensity ratio of the characteristic peak of 2θ in the range of 25.0° to 26.0° to the characteristic peak of 2θ in the range of 17.0° to 19.0° is 0.1 to 0.3. In this application, the peak of 2θ in the range of 17.0° to 19.0° is the diffraction peak of the matrix.

[0014] According to some embodiments of this application, the Raman spectrum of the cathode material is at 100 cm⁻¹. -1 Up to 140cm -1 And 50cm -1 Up to 90cm -1 It exhibits Raman shift peaks within the range. In this application, 100 cm⁻¹... -1 Up to 140cm -1 Raman shift peaks within the range represent characteristic peaks of the matrix, 50 cm⁻¹ -1 Up to 90cm -1 The Raman shift peaks within the specified range represent characteristic peaks of lithium iodate. This indicates that lithium iodate exists on the surface of the matrix, thereby improving the surface stability of the cathode material.

[0015] According to some embodiments of this application, the X-ray near-edge absorption spectrum of the cathode material has absorption peaks in the ranges of 56 eV to 58 eV and 60 eV to 62 eV. In this application, the absorption peak in the range of 56 eV to 58 eV represents lithium iodate, and the absorption peak in the range of 60 eV to 62 eV represents the matrix. This indicates that lithium iodate is present on the surface of the matrix, thereby improving the surface stability of the cathode material.

[0016] According to some embodiments of this application, the mass percentage of iodine in the cathode material is 0.2% to 5%. An iodine content within this range can improve the interfacial stability of the cathode material with the electrolyte under high temperature and high voltage, thereby suppressing gas generation during storage in the electrochemical device under high temperature and high pressure conditions and improving the high-temperature cycling performance of the electrochemical device. Simultaneously, it can reduce the valence state of the surface transition metal redox couple, increase electron hopping paths, and improve electronic conductivity, thereby enhancing the kinetic performance of the cathode material and further improving the temperature rise of the electrochemical device under high-rate charge-discharge conditions.

[0017] According to some embodiments of this application, the lithium element content by mass is greater than or equal to 5% based on the mass of the cathode material. In some embodiments, the lithium element content by mass is less than or equal to 8% based on the mass of the cathode material.

[0018] According to some embodiments of this application, the mass percentage content of nickel is greater than or equal to 30% based on the mass of the cathode material. In some embodiments, the mass percentage content of nickel is less than or equal to 60% based on the mass of the cathode material.

[0019] This application also provides a method for preparing the above-mentioned cathode material, which includes mixing a cathode material matrix with lithium iodide and calcining to obtain the cathode material. According to some embodiments of this application, the calcination temperature is 300°C to 700°C, for example, 350°C, 450°C, 550°C, or 650°C. In some embodiments, the calcination temperature is 400°C to 600°C. In some embodiments, the calcination is carried out in an inert atmosphere, such as a nitrogen atmosphere.

[0020] According to some embodiments of this application, the total molar number of metal elements other than Li in the matrix is ​​n. M The number of moles of Ni in the matrix is ​​n Ni The number of moles of Co in the matrix is ​​n Co The number of moles of element R in the matrix is ​​n R , 0 < n Ni / n M ≤1, 0≤n Co / n M <1, 0≤n R / n M<1, where R is an element selected from sodium (Na), magnesium (Mg), aluminum (Al), titanium (Ti), zirconium (Zr), niobium (Nb), yttrium (Y), chromium (Cr), vanadium (V), germanium (Ge), molybdenum (Mo), iron (Fe), copper (Cu), zinc (Zn), gallium (Ga), silver (Ag), tungsten (W), indium (In), tin (Sn), lead (Pb), antimony (Sb), lanthanum (La), cerium (Ce), calcium (Ca), or strontium (Sr). According to some embodiments of this application, 0.5 ≤ n Ni / n M ≤1, 0≤n Co / n M ≤0.5, 0≤n R / n M ≤0.5.

[0021] In a second aspect, this application provides an electrochemical device comprising a positive electrode, the positive electrode comprising a positive electrode current collector and a positive electrode active material layer, wherein the positive electrode active material layer comprises the positive electrode material of the first aspect.

[0022] In a third aspect, this application provides an electronic device that includes the electrochemical device of the second aspect.

[0023] This application improves the structural stability of the cathode material under high temperature and high pressure, as well as its kinetic performance under high rate charge and discharge conditions, by introducing iodine ion lattice doping into the surface layer of the cathode material and controlling the molar ratio of iodine to nickel within the range of 0.25 to 1.5. This reduces the gas generation during storage under high temperature and high pressure and the temperature rise under high rate charge and discharge conditions in the electrochemical device, thereby improving the overall performance of the electrochemical device. Attached Figure Description

[0024] Figure 1 This is a schematic diagram of the crystal structure of the cathode material according to one embodiment of this application.

[0025] Figure 2 This is the EDX spectrum of the cathode material in Example 3 of this application.

[0026] Figure 3 This is a SEM image of the cathode material of Example 3 of this application.

[0027] Figure 4 The images show the XRD patterns of the cathode materials of Example 8 and Comparative Example 1 of this application.

[0028] Figure 5 The X-ray near-edge absorption spectra of the cathode materials of Example 8 and Comparative Example 1 of this application are shown.

[0029] Figure 6 Raman diagrams of the cathode materials of Example 8 and Comparative Example 1 of this application. Detailed Implementation

[0030] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. The embodiments described herein are illustrative in nature and are used to provide a basic understanding of this application. The embodiments of this application should not be construed as limiting this application.

[0031] For the sake of brevity, this article only discloses a few specific numerical ranges. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, just as any upper limit can be combined with any other upper limit to form an unspecified range. Furthermore, each individually disclosed point or single value can itself serve as a lower or upper limit and be combined with any other point or single value or with other lower or upper limits to form an unspecified range.

[0032] In this description, unless otherwise stated, "above" and "below" include the stated number.

[0033] Unless otherwise stated, the terms used in this application have their common meanings as commonly understood by those skilled in the art. Unless otherwise stated, the values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (e.g., they can be tested according to the methods given in the embodiments of this application).

[0034] The list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms can mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another instance, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.

[0035] In a first aspect, this application provides a cathode material comprising a substrate and a first region located on the surface of the substrate, wherein the molar ratio of iodine to nickel in the first region is 0.25 to 1.5. Cathode ternary materials primarily generate capacity through the valence variation of nickel and cobalt. Under deep delithiation, the oxygen ion activity on the material surface is high, easily leading to side reactions with the electrolyte. On the one hand, spinel readily forms on the material surface, inhibiting lithium ion diffusion; on the other hand, surface side reactions further increase interfacial impedance and simultaneously cause gas generation on the material surface. The inventors of this application have discovered that by introducing iodine ion lattice doping into the surface layer of the cathode material and controlling the molar ratio of iodine to nickel to be 0.25 to 1.5, lithium iodate can be locally formed. Since lithium iodate possesses extremely strong oxidation resistance, as an external protective layer, it can improve the interfacial stability of the cathode material with the electrolyte under high temperature and high voltage conditions, thereby suppressing gas generation during storage in electrochemical devices under high temperature and high pressure conditions and improving the high-temperature cycling performance of electrochemical devices. At the same time, it can reduce the valence state of the surface transition metal redox couple, increase the electron jumping path, and improve the electronic conductivity, thereby improving the kinetic performance of the cathode material and thus improving the temperature rise of the electrochemical device under high-rate charge and discharge conditions.

[0036] According to some embodiments of this application, the molar ratio of iodine to nickel in the first region is 0.3, 0.4, 0.45, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, or a range of any two of these values. In some embodiments, the molar ratio of iodine to nickel in the first region is from 0.5 to 1.5.

[0037] In this application, "first region" may refer to a region extending from the outer surface of the cathode material to a depth of 100 nm in the cathode material.

[0038] According to some embodiments of this application, the first region includes a second region, wherein the second region includes lithium iodate.

[0039] According to some embodiments of this application, the first region further includes a third region, wherein the third region includes nickel iodide.

[0040] In some embodiments, the third region is located between the substrate and the second region. In this case, the second region, which includes lithium iodate on the outer side, has stronger oxidation resistance and can further improve the interfacial stability of the cathode material with the electrolyte under high temperature and high voltage, thereby suppressing gas generation during storage in the electrochemical device under high temperature and high pressure conditions and improving the high temperature cycling performance of the electrochemical device.

[0041] According to some embodiments of this application, the thickness of the second region is H2, where 10nm ≤ H2 ≤ 60nm. In some embodiments, H2 is a range of 13nm, 15nm, 17nm, 20nm, 23nm, 25nm, 27nm, 27nm, 29nm, 32nm, 35nm, 37nm, 40nm, 43nm, 45nm, 47nm, 50nm, 53nm, 55nm, 57nm, 59nm, or any combination of these values.

[0042] According to some embodiments of this application, the thickness of the third region is H3, where 2nm ≤ H3 ≤ 60nm. In some embodiments, H3 is 3nm, 5nm, 7nm, 9nm, 10nm, 12nm, 15nm, 17nm, 20nm, 23nm, 25nm, 27nm, 29nm, 32nm, 35nm, 37nm, 40nm, 43nm, 45nm, 47nm, 50nm, 55nm, or a range of any two of these values.

[0043] At this point, the appropriate thickness of the second and third regions can improve the interfacial stability of the cathode material with the electrolyte under high temperature and high voltage, while reducing the impact on the energy density of the electrochemical device.

[0044] According to some embodiments of this application, in the region from the surface of the positive electrode material to a depth of 2 μm from the surface of the positive electrode material, the molar ratio of iodine to nickel gradually decreases along the depth direction of the positive electrode material.

[0045] According to some embodiments of this application, the XRD pattern of the cathode material shows a characteristic peak of 2θ in the range of 25.0° to 26.0°. In this application, the peak of 2θ in the range of 25.0° to 26.0° is the diffraction peak of surface lithium iodate. At this time, the surface lithium iodate can better protect the surface of the substrate, improve the interfacial stability of the cathode material with the electrolyte under high temperature and high voltage, thereby suppressing gas generation during storage in the electrochemical device under high temperature and high pressure conditions and improving the high temperature cycling performance of the electrochemical device.

[0046] According to some embodiments of this application, in the XRD pattern of the cathode material, the peak intensity ratio of the characteristic peak of 2θ in the range of 25.0° to 26.0° to the characteristic peak of 2θ in the range of 17.0° to 19.0° is 0.1 to 0.3. In this application, the peak of 2θ in the range of 17.0° to 19.0° is the diffraction peak of the matrix.

[0047] According to some embodiments of this application, the Raman spectrum of the cathode material is at 100 cm⁻¹. -1 Up to 140cm -1 And 50cm -1Up to 90cm -1 It exhibits Raman shift peaks within the range. In this application, 100 cm⁻¹... -1 Up to 140cm -1 Raman shift peaks within the range represent characteristic peaks of the matrix, 50 cm⁻¹ -1 Up to 90cm -1 The Raman shift peaks within the specified range represent characteristic peaks of lithium iodate. This indicates that lithium iodate exists on the surface of the matrix, thereby improving the surface stability of the cathode material.

[0048] According to some embodiments of this application, the X-ray near-edge absorption spectrum of the cathode material has absorption peaks in the ranges of 56 eV to 58 eV and 60 eV to 62 eV. In this application, the absorption peak in the range of 56 eV to 58 eV represents lithium iodate, and the absorption peak in the range of 60 eV to 62 eV represents the matrix. This indicates that lithium iodate is present on the surface of the matrix, thereby improving the surface stability of the cathode material.

[0049] According to some embodiments of this application, the mass percentage of iodine in the cathode material is 0.2% to 5%. An iodine content within this range can improve the interfacial stability of the cathode material with the electrolyte under high temperature and high voltage conditions, thereby suppressing gas generation during storage in the electrochemical device under high temperature and high pressure conditions and improving the high-temperature cycling performance of the electrochemical device. Simultaneously, it can reduce the valence state of the surface transition metal redox couple, increase electron jumping paths, and improve electronic conductivity, thereby enhancing the kinetic performance of the cathode material and improving the temperature rise of the electrochemical device under high-rate charge-discharge conditions.

[0050] According to some embodiments of this application, the lithium element content by mass is greater than or equal to 5% based on the mass of the cathode material. In some embodiments, the lithium element content by mass is less than or equal to 8% based on the mass of the cathode material.

[0051] According to some embodiments of this application, the mass percentage content of nickel is greater than or equal to 30% based on the mass of the cathode material. In some embodiments, the mass percentage content of nickel is less than or equal to 60% based on the mass of the cathode material.

[0052] This application also provides a method for preparing the above-mentioned cathode material, which includes mixing a cathode material matrix with lithium iodide and calcining to obtain the cathode material. According to some embodiments of this application, the calcination temperature is 300°C to 700°C, for example, 350°C, 450°C, 550°C, or 650°C. In some embodiments, the calcination temperature is 400°C to 600°C. In some embodiments, the calcination is carried out in an inert atmosphere, such as a nitrogen atmosphere.

[0053] According to some embodiments of this application, the total molar number of metal elements other than Li in the matrix is ​​n. M The number of moles of Ni in the matrix is ​​n Ni The number of moles of Co in the matrix is ​​n Co The number of moles of element R in the matrix is ​​n R , 0 < n Ni / n M ≤1, 0≤n Co / n M <1, 0≤n R / n M <1, where R is an element selected from sodium (Na), magnesium (Mg), aluminum (Al), titanium (Ti), zirconium (Zr), niobium (Nb), yttrium (Y), chromium (Cr), vanadium (V), germanium (Ge), molybdenum (Mo), iron (Fe), copper (Cu), zinc (Zn), gallium (Ga), silver (Ag), tungsten (W), indium (In), tin (Sn), lead (Pb), antimony (Sb), lanthanum (La), cerium (Ce), calcium (Ca), or strontium (Sr). According to some embodiments of this application, 0.5 ≤ n Ni / n M ≤1, 0≤n Co / n M ≤0.5, 0≤n R / n M ≤0.5.

[0054] Secondly, this application provides an electrochemical device including a positive electrode, which includes a positive electrode current collector and a positive electrode active material layer, wherein the positive electrode active material layer includes the positive electrode material of the first aspect.

[0055] According to some embodiments of this application, the positive electrode active material layer further includes a conductive agent and a binder. In some embodiments, the binder includes, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, or acrylated styrene-butadiene rubber, etc. In some embodiments, the conductive agent includes, but is not limited to: carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based material is selected from graphite, carbon black, acetylene black, Ketjen black, carbon nanotubes, carbon fibers, graphene, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fibers, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.

[0056] According to some embodiments of this application, the positive electrode further includes a positive electrode current collector, which can be a metal foil or a composite current collector. For example, aluminum foil can be used. The composite current collector can be formed by forming a metallic material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer substrate.

[0057] The electrochemical device of this application also includes a negative electrode, which includes a negative electrode active material layer and a negative electrode current collector.

[0058] According to some embodiments of this application, the negative electrode active material layer includes a negative electrode active material, a conductive agent, and a binder. In some embodiments, the negative electrode active material may include a material that reversibly inserts / deintercalates lithium ions, lithium metal, lithium metal alloys, or transition metal oxides. In some embodiments, the negative electrode active material includes at least one of carbon materials or silicon materials, wherein the carbon materials include at least one of graphite and hard carbon, and the silicon materials include at least one of silicon, silicon oxides, silicon carbide compounds, or silicon alloys. In some embodiments, the binder may include various adhesive polymers. In some embodiments, the binder includes at least one of polyvinylidene fluoride, a copolymer of polyvinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene, polyhexafluoropropylene, or styrene-butadiene rubber. In some embodiments, the conductive agent may be any conductive material, as long as it does not cause a chemical change. In some embodiments, the conductive agent includes at least one of conductive carbon black, acetylene black, carbon nanotubes, Ketjen black, carbon fibers, or graphene.

[0059] According to some embodiments of this application, the negative electrode current collector can be copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or a combination thereof.

[0060] The electrochemical device of this application also includes an electrolyte, which includes lithium salts and non-aqueous solvents.

[0061] In some embodiments of this application, the lithium salt is selected from one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB, and lithium difluoroborate. For example, LiPF6 can be selected as the lithium salt.

[0062] The non-aqueous solvent may be a carbonate compound, a carboxylic acid ester compound, an ether compound, other organic solvents, or a combination thereof.

[0063] The aforementioned carbonate compounds may be chain carbonate compounds, cyclic carbonate compounds, fluorocarbonate compounds, or combinations thereof.

[0064] Examples of the aforementioned chain carbonate compounds are dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), vinyl ethylene carbonate (VEC), and combinations thereof. Examples of fluorinated carbonate compounds are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate, and combinations thereof.

[0065] Examples of the above-mentioned carboxylic acid ester compounds are methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolide, valproic acid lactone, caprolactone, and combinations thereof.

[0066] Examples of the above-mentioned ether compounds are dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, and combinations thereof.

[0067] Examples of other organic solvents mentioned above include dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolium ketone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphate esters and combinations thereof.

[0068] According to some embodiments of this application, in this electrochemical device, a separator is provided between the positive and negative electrodes to prevent short circuits. The material and shape of the separator used in the embodiments of this application are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the separator comprises a polymer or inorganic material formed from a material stable to the electrolyte of this application. For example, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a nonwoven fabric, membrane, or composite membrane with a porous structure, and the material of the substrate layer includes at least one of polyethylene, polypropylene, polyethylene terephthalate, or polyimide. Specifically, a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane can be selected. At least one surface of the substrate layer is provided with a surface treatment layer, which can be a polymer layer or an inorganic layer, or a layer formed by mixing polymers and inorganic materials. The inorganic layer comprises inorganic particles and a binder. The inorganic particles include at least one of alumina, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate. The binder includes at least one of polyvinylidene fluoride, a copolymer of polyvinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, or polyhexafluoropropylene. The polymer layer contains a polymer, the polymer material of which includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, or poly(vinylidene fluoride-hexafluoropropylene).

[0069] According to some embodiments of this application, the electrochemical device of this application includes, but is not limited to, all types of primary or secondary batteries. In some embodiments, the electrochemical device is a lithium secondary battery. In some embodiments, the lithium secondary battery includes, but is not limited to, lithium metal secondary batteries, lithium-ion secondary batteries, lithium polymer secondary batteries, or lithium-ion polymer secondary batteries.

[0070] Thirdly, the electronic device of this application can be any device that uses the electrochemical device of the second aspect of this application.

[0071] In some embodiments, the electronic device includes, but is not limited to: laptop computers, pen input computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries or lithium-ion capacitors, etc.

[0072] Examples and Comparative Examples

[0073] 1. Preparation of cathode materials

[0074] Step 1: Prepare a mixed solution containing NiSO4 and CoSO4 according to the elemental molar ratio Ni:Co = 98:2. Mix this solution with a precipitant (NaOH solution) and a complexing agent (ammonia water) and react them. Control the reaction time to 40 hours, the ammonia water concentration to 2.5 mol / L, and the pH to 13 to obtain the ternary precursor Ni. 0.98 Co 0.02 (OH)2;

[0075] Step 2: The ternary precursor Ni from Step 1 0.98 Co 0.02 (OH)₂ and lithium hydroxide were ground and mixed evenly at a molar ratio of 1:1.05, calcined at 680℃ in an oxygen atmosphere for 20 hours, cooled to room temperature at a rate of 10℃ / min, and finally crushed and sieved to obtain the cathode material intermediate LiNi. 0.98 Co 0.02 O2;

[0076] Step 3: The positive electrode material intermediate LiNi from Step 2 0.98 Co 0.02 O2 and LiI are mixed in a certain ratio (see Table 1 for the specific mixing ratio, where the amount of LiI added is relative to the mass of the cathode material intermediate), and then sintered at a certain temperature (see Table 1 for the specific temperature) under N2 environment to obtain the cathode material.

[0077] Table 1

[0078]

[0079] 2. Preparation of lithium-ion batteries

[0080] (1) Preparation of lithium-ion button batteries

[0081] A positive electrode slurry is prepared by thoroughly mixing a binder polyvinylidene fluoride (PVDF), a conductive agent conductive carbon black (Super P), and a positive electrode material in a certain weight ratio (5:5:95) in N-methylpyrrolidone (NMP).

[0082] The positive electrode slurry was uniformly coated onto aluminum foil, with a single-sided coating thickness of 40 μm. After drying, it was rolled to form the desired electrode, wherein the areal density of the coated electrode was 14 mg / cm³. 2 They are then punched into 14mm diameter discs to prepare single-sided positive electrode sheets;

[0083] The separator is punched into a circular piece with a diameter of 18 mm; the negative electrode used is a lithium metal sheet with a diameter of 18 mm; LiPF6 is added to a solvent composed of propylene carbonate (PC), ethylene carbonate (EC), and diethyl carbonate (DEC) in a weight ratio of 1:1:1 and mixed evenly to obtain an electrolyte, wherein the mass concentration of LiPF6 is 12.5% ​​based on the mass of the electrolyte.

[0084] Move the positive electrode, separator, negative electrode (lithium sheet), electrolyte, battery casing and other accessories into the glove box (the water content must be less than 11ppm);

[0085] The batteries are assembled in a bottom-to-top stacking order and then injected with electrolyte. They are then packaged on a packaging machine to obtain button cells.

[0086] (2) Preparation of lithium-ion pouch batteries

[0087] Preparation of positive electrode

[0088] A positive electrode slurry is prepared by thoroughly mixing a binder polyvinylidene fluoride (PVDF), a conductive agent conductive carbon black (SuperP), and a positive electrode material in a certain weight ratio (1.5:1.5:97) in N-methylpyrrolidone (NMP).

[0089] The positive electrode slurry was uniformly coated onto aluminum foil, with a single-sided coating thickness of 40 μm, and double-sided coating was also performed. After drying, the electrode was rolled to form the desired electrode, with a coating surface density of 14 mg / cm³. 2 .

[0090] Preparation of negative electrode

[0091] Artificial graphite, styrene-butadiene rubber, and sodium carboxymethyl cellulose (CMC) were mixed with deionized water at a mass ratio of 96:2:2 and stirred until homogeneous to obtain a negative electrode slurry. This negative electrode slurry was then coated onto a 12 μm thick copper foil. After drying and cold pressing, the foil was cut and tabs were welded to obtain the negative electrode.

[0092] Preparation of electrolyte

[0093] In a dry argon atmosphere, LiPF6 was added to a solvent composed of propylene carbonate (PC), ethylene carbonate (EC), and diethyl carbonate (DEC) in a weight ratio of 1:1:1 and mixed thoroughly to obtain an electrolyte. The mass concentration of LiPF6 was 12.5% ​​based on the mass of the electrolyte.

[0094] Preparation of the separating membrane

[0095] Polyethylene (PE) porous polymer film is used as the separator.

[0096] Preparation of lithium-ion batteries

[0097] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes for isolation. The electrode assembly is then wound to form the electrode assembly. This assembly is placed in an outer aluminum-plastic film package, electrolyte is injected, and the package is sealed. After formation, degassing, and edge trimming processes, a lithium-ion pouch battery is obtained.

[0098] Test methods

[0099] 1. Testing of iodine, nickel, and lithium content in cathode materials

[0100] (1) Test of the content of each element in the surface layer

[0101] The concentration and molar ratio of Ni and I elements at a depth of 0-100 nm were tested using XPS combined with ion polishing.

[0102] (2) Element content test in cathode material

[0103] The content of each element was obtained through ICP testing.

[0104] 2. Thickness testing of the second and third regions in the cathode material.

[0105] The lithium-ion battery is at 10mA / cm 2 The sample was fully discharged to below 3.5V at a current density and allowed to stand for 10 minutes before being disassembled in a glove box to obtain the positive electrode. The positive electrode was then transferred to a scanning electron microscope (SEM) equipped with a focused ion beam (model: FEI VionPlasma FIB) to process a sample suitable for analysis using a transmission scanning electron microscope (STEM, model: FEI Titan3 G260-300). The sample surface was required to be protected with Pt and processed with a Ga ion beam, with a sample thickness not exceeding 100 nm. The sample was then cleaned using a low-voltage mode to remove any residual surface material from the processing.

[0106] The sample was observed under STEM, and the thickness of the second and third regions was measured. Samples were collected from at least three different locations, and the average value was taken.

[0107] 3. XRD peak intensity ratio test

[0108] The XRD pattern of the cathode material was obtained by XRD diffraction test. The strongest peak intensity of 2θ in the range of 25.0° to 26.0° is I1, and the strongest peak intensity of 2θ in the range of 17.0° to 19.0° is I2. The XRD peak intensity ratio is I1 / I2.

[0109] 4. Raman spectroscopy and X-ray near-edge absorption spectroscopy

[0110] The cathode material was tested using Raman spectroscopy and X-ray near-edge absorption spectroscopy to determine whether a 50 cm⁻¹ region was present in the Raman spectrum. -1 Up to 90cm -1 Does the Raman shift peak within the range and the X-ray near-edge absorption spectrum contain absorption peaks in the range of 56 eV to 58 eV?

[0111] Thickness expansion rate test at 5.85℃

[0112] The lithium-ion pouch battery was charged to 4.35V at 0.5C at 25℃, and then charged at a constant voltage of 4.35V to 0.05C. The thickness of the lithium-ion battery at this point was measured and recorded using a micrometer and denoted as H. 11 The lithium-ion battery was then placed in an 85°C oven for 12 hours. After 12 hours, the thickness of the lithium-ion battery was measured and recorded using a micrometer, denoted as H. 12 .

[0113] Thickness expansion rate (%) of lithium-ion battery after storage at 85℃ for 12 hours = (H 12 -H 11 ) / H 11 ×100%.

[0114] 6.45℃ Cyclic Capacity Retention Test

[0115] The lithium-ion pouch battery was placed in a 45°C constant temperature chamber and left to stand for 30 minutes to allow it to reach a constant temperature. The lithium-ion battery that had reached a constant temperature was then charged at 1.5C at 45°C to 4.35V, and then charged at 4.35V at a constant voltage to 0.02C. It was then discharged at 4C at a constant current to 3.0V. The discharge capacity of this discharge cycle was recorded as the first cycle discharge capacity. The battery was charged and discharged in this manner for 300 cycles. The discharge capacity of the battery after the 300th cycle was recorded as the 300th cycle discharge capacity.

[0116] The capacity retention rate (%) of a lithium-ion battery after 300 cycles at 45°C = (300th cycle discharge capacity / first cycle discharge capacity) × 100%.

[0117] 7.1.5C / 8C discharge temperature rise

[0118] The lithium-ion pouch battery was placed in a 25°C constant temperature chamber and left to stand for 30 minutes to allow it to reach a constant temperature. The battery was then charged at a constant current of 1.5C to a voltage of 4.35V, followed by constant voltage charging at 4.35V to a current of 0.05C. Finally, it was discharged at a constant current of 8C to 3.0V. During this process, the lithium-ion battery was wrapped in heat-insulating cotton, and the temperature at the top, bottom, and middle of the battery was measured using a multi-channel temperature measuring instrument, and the average value was taken.

[0119] 8. Gram Capacity Test

[0120] In an environment of 25℃, a coin cell lithium-ion battery is charged at a constant current and constant voltage of 0.5C until the upper limit voltage is 4.25V, and then discharged at a constant current of 0.2C until the final voltage is 2.8V. Calculate the discharge capacity of the lithium-ion battery. Calculate the ratio of the discharge capacity of the lithium-ion battery to the mass of the positive electrode material, denoted as the specific capacity of the lithium-ion battery.

[0121] Test Results

[0122] Table 2-1

[0123]

[0124] Note: H2 is the thickness of the second region including lithium iodate; H3 is the thickness of the third region including nickel iodide.

[0125] Table 2-2

[0126]

[0127] As can be seen from the comparison of Examples 1 to 9 with Comparative Examples 1 to 3 in Tables 2-1 and 2-2, when the molar ratio of iodine to nickel on the surface of the cathode material is in the range of 0.25 to 1.5, the lithium-ion battery exhibits excellent high-temperature storage performance, high-temperature cycle performance, and lower temperature rise under high-rate charge-discharge conditions. A possible reason is that when the molar ratio of iodine to nickel on the surface of the cathode material is in the range of 0.25 to 1.5, lithium iodate can be locally formed. Since lithium iodate has extremely strong oxidation resistance, as an external protective layer, it can improve the interfacial stability between the cathode material and the electrolyte under high temperature and high voltage, thereby suppressing gas generation during storage under high temperature and high pressure conditions and improving the high-temperature cycle performance of the lithium-ion battery. Simultaneously, it can reduce the valence state of the transition metal redox couple on the surface, increase electron jumping paths, and improve electronic conductivity, thereby improving the kinetic performance of the cathode material and thus improving the temperature rise of the lithium-ion battery under high-rate charge-discharge conditions.

[0128] When the molar ratio of iodine to nickel is too low (Comparative Example 2), the high-temperature storage performance, high-temperature cycle performance, and rate performance of lithium-ion batteries cannot be effectively improved because a local lithium iodate coating layer cannot be formed.

[0129] When the molar ratio of iodine to nickel is too high (Comparative Example 3), although it can effectively improve the high-temperature storage performance and high-temperature cycle performance of lithium-ion batteries, the excessive amount of iodine forms a heterogeneous structure that coats the surface of the positive electrode active material, hindering the diffusion of lithium ions. This results in a severe temperature rise of the lithium-ion battery under high-rate charge and discharge conditions.

[0130] While some exemplary embodiments of this application have been described and illustrated, this application is not limited to the disclosed embodiments. Rather, those skilled in the art will recognize that modifications and changes may be made to the described embodiments without departing from the spirit and scope of this application as described in the appended claims.

Claims

1. A cathode material, comprising a substrate and a first region located on the surface of the substrate, wherein the molar ratio of iodine to nickel in the first region is 0.25 to 1.5; the first region includes a second region, the second region comprising lithium iodate; Based on the mass of the cathode material, the mass percentage content of the iodine element is 0.2% to 5%; Based on the mass of the cathode material, the mass percentage of nickel is 30% to 60%.

2. The cathode material according to claim 1, wherein, The molar ratio of iodine to nickel in the first region is 0.5 to 1.

5.

3. The cathode material according to claim 1, wherein, The first region further includes a third region comprising nickel iodide, and the cathode material satisfies at least one of the following conditions (a) to (c): (a) The third region is located between the substrate and the second region; (b) The thickness of the second region is H2, where 10nm ≤ H2 ≤ 60nm; (c) The thickness of the third region is H3, where 2nm≤H3≤60nm.

4. The cathode material according to claim 1, wherein, From the surface of the cathode material to a depth of 2 μm from the surface of the cathode material, the molar ratio of iodine to nickel gradually decreases along the depth direction of the cathode material.

5. The cathode material according to claim 1, wherein, In the XRD pattern of the cathode material, 2θ has a characteristic peak in the range of 25.0° to 26.0°.

6. The cathode material according to claim 5, wherein, In the XRD pattern of the cathode material, the peak intensity ratio of the characteristic peak of 2θ in the range of 25.0° to 26.0° to the characteristic peak of 2θ in the range of 17.0° to 19.0° is 0.1 to 0.

3.

7. The cathode material according to claim 1, wherein, The cathode material satisfies at least one of the following conditions (d) to (e): (d) The Raman spectrum of the cathode material at 100 cm⁻¹ -1 Up to 140cm -1 And 50cm -1 Up to 90cm -1 It has Raman shift peaks within the range; (e) The X-ray near-edge absorption spectrum of the cathode material has absorption peaks in the ranges of 56eV to 58eV and 60eV to 62eV.

8. The cathode material according to claim 1, wherein, The cathode material satisfies at least one of the following conditions (g) and (i): (g) Based on the mass of the cathode material, the mass percentage of lithium element is 5% to 8%; (i) The total number of moles of metal elements other than lithium in the matrix is ​​n. M The number of moles of nickel in the matrix is ​​n. Ni The number of moles of cobalt in the matrix is ​​n. Co The number of moles of element R in the matrix is ​​n. R , 0 < n Ni / n M ≤1, 0≤n Co / n M <1, 0≤n R / n M <1, wherein the R element includes at least one of sodium, magnesium, aluminum, titanium, zirconium, niobium, yttrium, chromium, vanadium, germanium, molybdenum, iron, copper, zinc, gallium, silver, tungsten, indium, tin, lead, antimony, lanthanum, cerium, calcium, or strontium.

9. An electrochemical device comprising a positive electrode, the positive electrode comprising a positive electrode current collector and a positive electrode active material layer, the positive electrode active material layer comprising the positive electrode material according to any one of claims 1 to 8.

10. An electronic device comprising the electrochemical device of claim 9.

Citation Information

Patent Citations

  • Positive-electrode active material for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery including the same

    CN104518211A